An introduction to Participatory Value Evaluation - Niek Mouter; Paul Koster; Thijs Dekker (Tinbergen Institute, 2019)
Cost-Benefit Analysis (CBA) for public policies assumes `consumer sovereignty', implying that impacts of government projects can be expressed in monetary terms by aggregating individuals' willingness to pay. However, individuals' willingness to pay might not accurately reflect preferences towards public policies. Participatory Value Evaluation (PVE) is a novel evaluation framework specifically designed to rectify this issue by going beyond the paradigm of `consumer sovereignty'. PVE infers the social welfare effects of public policies through eliciting individuals' preferences over the allocation of public budgets (`citizen sovereignty') as well as their private income (`consumer sovereignty'). In a PVE, individuals are asked to choose the best portfolio of projects with corresponding impacts for society and themselves subject to governmental and private budget constraints. This paper positions PVE relative to past innovations in applied welfare economics and illustrates the potential of the approach through a case study on projects to mitigate flood risks at locations along the Dutch river `Waal'. In total 2,900 citizens participated in this PVE. The main result of the case study is that citizens have a preference for projects that combine strengthening dikes and giving the river space to flood safely, particularly when such projects positively influence biodiversity and recreational opportunities.
Keywords: D71; D61; D63; 330; Participatory Value Evaluation; Cost-Benefit Analysis; Benefit-Cost Analysis; Citizen Participation; Environmental Valuation; Flood Protection; Biodiversity